2008
DOI: 10.1186/cc7157
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, organ dysfunction and mortality in severe sepsis: a Spanish multicentre study

Abstract: IntroductionSepsis is a leading cause of admission to non-cardiological intensive care units (ICUs) and the second leading cause of death among ICU patients. We present the first extensive dataset on the epidemiology of severe sepsis treated in ICUs in Spain.MethodsWe conducted a prospective, observational, multicentre cohort study, carried out over two 3-month periods in 2002. Our aims were to determine the incidence of severe sepsis among adults in ICUs in a specific area in Spain, to determine the early (48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
276
4
21

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(332 citation statements)
references
References 32 publications
22
276
4
21
Order By: Relevance
“…During severe sepsis or septic shock, development of organ dysfunction dramatically increases morbidity and mortality [93] . During the acute phase of sepsis or septic shock, circulatory failure is discussed as the predominant cause of death [94,95] . However, underlying mechanisms leading to organ failure are not fully understood yet.…”
Section: Biomarkers Of Tissue Dysfunction and Organ Failurementioning
confidence: 99%
“…During severe sepsis or septic shock, development of organ dysfunction dramatically increases morbidity and mortality [93] . During the acute phase of sepsis or septic shock, circulatory failure is discussed as the predominant cause of death [94,95] . However, underlying mechanisms leading to organ failure are not fully understood yet.…”
Section: Biomarkers Of Tissue Dysfunction and Organ Failurementioning
confidence: 99%
“…In Spain, an estimated 40,000 cases of severe sepsis and 12,000 sepsis-related deaths occur each year [4,5]. The Surviving Sepsis Campaign (SSC) protocol was developed as an international initiative to reduce mortality due to severe sepsis and is promoted by several critical care societies [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…(20,21) Early reports using conventional echocardiography suggested that increased enddiastolic volume and reduced ejection fraction was associated with an improved prognosis and could be considered as an adaptive change. However a meta-analysis of 14 studies looking at studies of ventricular volumes and dysfunction published up to 2012 has shown that survivors had lower ejection fractions and that there is no significant differences in LVEF or RVEF or in RV dimensions between survivors and non-survivors from severe sepsis or septic shock.…”
Section: Prognosismentioning
confidence: 99%